Behavior change analysis due to violent video gaming using deep learning models - Rahman, Akhlak Ur; Raj, Fahad Khan; Afnan, Monthasir Delwar; Rahad, Rakib Hasan; Ahmed, Md. Samir Uddin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.